Tropomyosin isoforms have specific effects on the transcriptome of undifferentiated and differentiated B35 neuroblastoma cells. Issue 4 (19th February 2018) - Stefen, Holly; Suchowerska, Alexandra Kalyna; Chen, Bei Jun; Brettle, Merryn; Kuschelewski, Jennifer; Gunning, Peter William; Janitz, Michael; Fath, Thomas
Abstract : Tropomyosins, a family of actin‐associated proteins, bestow actin filaments with distinct biochemical and physical properties which are important for determining cell shape and regulating many cellular processes in eukaryotic cells. Here, we used RNA‐seq to investigate the effect of four tropomyosin isoforms on gene expression in undifferentiated and differentiated rat B35 neuroblastoma cells. In undifferentiated cells, overexpression of tropomyosin isoforms Tpm1.12, Tpm2.1, Tpm3.1, and Tpm4.2 differentially regulates a vast number of genes, clustering into several gene ontology terms. In differentiated cells, tropomyosin overexpression exerts a much weaker influence on overall gene expression. Our findings are particularly compelling because they demonstrate that tropomyosin‐dependent changes are attenuated once the cells are induced to follow a defined path of differentiation. Database: Sequence data for public availability are deposited in the European Nucleotide Archive under the accession number PRJEB24136. Abstract : We carried out a transcriptomic analysis of B35 neuroblastoma cells, stably expressing different isoforms of the actin‐associated protein tropomyosin. Our analysis demonstrates that tropomyosin overexpression in undifferentiated B35 cells leads to major changes of the transcriptome. This effect is largely reduced when the cells are induced for differentiation.